TEKNIK DAN MANAJEMEN PRODUKSI BIBIT BABI DI BANJAR DAUH UMA, DESA PENGOTAN, KABUPATEN BANGLI - NLG SUMARDANI; IGA ARTA PUTRA; IW SUBERATA; IG SURANJAYA; DK HARYA PUTRA; WS YUPARDHI (Buletin Udayana Mengabdi, 2015)
The short course of management of animal husbandry and using Artificial Insemination (AI) on swine wasconducted on September 6th 2014 at Dauh Uma Pengotan Village, Regency of Bangli. There were 15 farmers whomerged into group as participants of this activity. The aimed of this activity was to increase litter size of swinewith AI program in breeding management. The used method of activity was giving counseling about breedingand health management of animal husbandry in breeding farm, AI program, and then practiced inseminate onswine. Based on the process of short course it was concluded that, the response of participants on AI was veryenthusiastic in joining the activity.Keywords : animal husbandry, breeding, artificial insemination, litter size, swine.